Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pengunjung Pada Kolam Jati Alam Asri Kalianda - Sukri, Sukri; Saodin, Saodin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Businesses in the tourism services sector are very promising, many entrepreneurs are opening tourism services businesses. Therefore, providing services will increase dedication for the better, namely with the aim of creating visitor satisfaction with the services provided, so that visitors will feel satisfied when visiting the tourist attraction. This research aims to determine the influence of service quality on visitor satisfaction at the Jati Alam Asri Kalianda Pool. To determine the influence of facilities on visitor satisfaction at the Jati Alam Asri Kalianda Pool. The sampling technique used was accidental sampling technique, the sample used was 96 respondents while the analytical tools used were multiple linear regression analysis, classical assumption test, t test, F test and coefficient of determination (R2). Based on the results of this research, it is known that the coefficient of determination (R2) = 0.395, it can be said that 39.5% of the variables of service quality (X1) and facilities (X2) influence visitor satisfaction, while the remaining 60.5% is due to the influence of other variables that are not covered in this research. The results of the F test showed that the calculated F value was 32,066, while the F table at the 5% significance level was 3.09. It turned out that the calculated F was greater than the F table, so the ho or null hypothesis was rejected so that it was concluded that the service quality (X1) and facility (X2) variables had jointly significant influence on visitor satisfaction. The results of the t test analysis show that the service quality variable has a positive and significant influence on visitor satisfaction and the facility variable has a positive and significant influence on visitor satisfaction.